Flu vaccination among health workers in Italy: results from the nationwide surveillance PASSI 2015-18. (30th September 2020) - Gallo, R; Minardi, V; Contoli, B; Possenti, V; Carrozzi, G; Trinito, M O; Ramigni, M; Fateh-Moghadam, P; Masocco, M; D'Andrea, E
Abstract: Background: Influenza causes a significant health and socio-economic burden every year. Healthcare workers (HCWs) are at higher risk of exposure to respiratory pathogens than general population, including seasonal influenza virus, with potential threats to their health and patients' safety. We aimed to estimate the adherence to flu vaccination of health workers in 2015-2018 seasons in Italy. Methods: We analyzed data collected between 2015 and 2018 from the Italian Behavioral Risk Factor Surveillance System (PASSI). PASSI collects data on health behaviors in the adults (18-64 years) through telephonic administration of standardized questionnaires to a representative sample of Italian population. The answers related to flu vaccination refer to the vaccination campaign preceding the interview Results: Preliminary data show that overall 11.9% (CI 10.3% - 13.7%) of HCWs reported to have been vaccinated vs 7.2% (CI 6.9% - 7.5%) of the total population sample. Physicians showed a higher overall adherence compared to other healthcare professionals (22.4% [CI 18% - 27.5%] vs 9% [CI 7.4% - 10.9%], respectively). Differences of adherence were found also across age groups: 18.3% [CI 15% - 22.2%] of respondents between 50-64 years reported to have received a vaccination compared to 10% (CI 7.9% - 12.5%) and 4.3% (CI 2.8% - 6.4%) of 35-49 years and 18-34 years age groups, respectively. The annual influenza vaccination coverage for people working in healthcare has increased over the years (9.8% in 2015 vs 14.1% in 2018). Conclusions: Although coverage rates are increasing over time, adherence to influenza vaccination is still too low, especially among younger HCWs and non-medical HCWs. Strategic actions, such as local and national programs to increase self-awareness of being an at-high-risk category for contracting and transmitting infections and/or mandatory vaccination, should be adopted to sharply achieve an optimal coverage rate for HCWs. Key messages: Adherence to seasonal influenza vaccination is still very low among Italian HCWs. A participatory attitude towards vaccination for HCWs should be pursued. Monitoring and reporting process should be improved to provide further detailed evidence for adopting targeted programs.